Penicillin Allergy De-labeling Results in Significant Changes in Outpatient Antibiotic Prescribing Patterns - Hills, Thomas; Arroll, Nicola; Duffy, Eamon; Capstick, Janice; Jordan, Anthony; Fitzharris, Penny (Frontiers in Allergy, 2020)
Unverified penicillin allergies are common but most patients with a penicillin allergy label can safely use penicillin antibiotics. Penicillin allergy labels are associated with poor clinical outcomes and overuse of second-line antibiotics. There is increasing focus on penicillin allergy “de-labeling” as a tool to improve antibiotic prescribing and antimicrobial stewardship. The effect of outpatient penicillin allergy de-labeling on long-term antibiotic use is uncertain. We performed a retrospective pre- and post- study of antibiotic dispensing patterns, from an electronic dispensing data repository, in patients undergoing penicillin allergy assessment at Auckland City Hospital, New Zealand. Over a mean follow-up of 4.55 years, 215/304 (70.7%) of de-labeled patients were dispensed a penicillin antibiotic. Rates of penicillin antibiotic dispensing were 0.24 (0.18–0.30) penicillin courses per year before de-labeling and 0.80 (0.67–0.93) following de-labeling with a reduction in total antibiotic use from 2.30 (2.06–2.54) to 1.79 (1.59–1.99) antibiotic courses per year. In de-labeled patients, the proportion of antibiotic courses that were penicillin antibiotics increased from 12.81 to 39.62%. Rates of macrolide, cephalosporin, trimethoprim/co-trimoxazole, fluoroquinolone, “other” non-penicillin antibiotic use, and broad-spectrum antibiotic use were all lower following de-labeling. Further, antibiotic costs were lower following de-labeling. In this study, penicillin allergy de-labeling was associated with significant changes in antibiotic dispensing patterns.